Pedigree vs. Grit : predicting mutual fund manager performance - Eso?, Peter, (SAGE Knowledge. Cases., 2017)
An asset management company must replace the manager of its two signature mutual funds, who is about to retire. Two candidates have been short-listed. The management team is divided and cannot decide which of the two candidates would make the better mutual fund manager. The retiring manager presents a linear regression model to examine success factors of mutual fund managers. This linear regression is the starting point for the subsequent analysis.